Accommodation Costs in State University Dormitories Illustrated by Selected Examples - Kulczyk-Dynowska, Alina; Kubicz, Marcelina (Koszty zakwaterowania w akademikach publicznych na przykładzie wybranych ofert, 2024)
Purpose: The main purpose of the article was to present accommodation offered by selected sixteen state universities located in the following cities: Warsaw, Cracow, Poznań, Wrocław, Łódź, Gdańsk, Toruń. A supplementary objective was to draw attention to the fact that student dormitories constitute a specific product within the real estate market. Methodology: The first stage of the study consisted in a literature query. Next, using the direct observation method, a database comprising accommodation offered by the selected universities was created. The database includes 155 observations. As a result of applying the three sigma rule, two outlier observations were discarded, while the rest were analysed using statistical methods. Findings: The university function makes the real estate market of university cities a specific one and requires appropriate spatial management. The accommodation offered by the analysed universities remains highly diverse and varies considerably in price, despite the fact that all the dormitories are among public resources. Investment is required to adapt the provided accommodation to the needs of people with disabilities. Implications and recommendations: It seems that state universities should consider organizing an information campaign addressing the prices of accommodation – primarily those competitively priced. In the period featuring a declining number of students, such a factor can significantly promote a particular university. Originality/value: The results of the research are useful for both students and university administration.
Prace Naukowe Uniwersytetu Ekonomicznego we Wrocławiu = Research Papers of Wrocław University of Economics; 2024; vol. 68, nr 2, s. 95-105
Keywords: reaal estate market; student dormitory; rental costs; rynek nieruchomościami; akademik; koszty najmu